(NgEO\LEKTRI^ESKIE RAZREZY @GA sIBIRI I mONGOLII (B/s - (NdORVIEW(B, (Nw(B. (Ns(B.s; (NaDWOKATOW(B, (Nw(B. (Nr(B.s; (NbODIEW(B, (Nb(B.(Nb(B.s; (NcYDYPOW(B, (N~(B.(Nc(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B. 140 (NNAZW(B.s
(Nan sssr(B. (NsIBIRSKOE OTD(B. (NbURQTSKIJ FILIAL(B. (NiNSTITUT ESTESTWENNYH NAUKs
Keywords: (NgEOLOGIQs